IJPE 2019
DOI: 10.23940/ijpe.19.07.p17.19051911
|View full text |Cite
|
Sign up to set email alerts
|

7A52 Aluminum Alloy MIG Welding Residual Stress Reliable Measurement based on Hole-Drilling Method

Abstract: To analyze the welding residual stress distributions for aluminum alloy medium and thick plates after the process of MIG welding, a residual stress testing system based on hole-drilling method was designed by virtual instrument and NI data acquisition card. To improve the accuracy and reliability of measurement results, the elasticity modulus error, strain gauge pasted error, and strain reading value time error were emphatically analyzed. The elasticity modulus error could be corrected by the curve that is fit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
(9 reference statements)
0
1
0
1
Order By: Relevance
“…Guo et al (2019) citam que as pesquisas em torno da medições de tensões residuais que vêm ganhando destaque atualmente são justamente visando a busca por otimizar a calibração dos métodos que envolvem a interferência humana e, assim, melhorar sua usabilidade. Já para Gan et al (2018), erros no módulo de elasticidade e das leituras das deformações plásticas podem acarretar em divergências de valores entre as tensões calculadas. Além de que, para Kumar (2021), deformação plástica muda permanentemente a dimensão e a forma do metal, sendo que em termos de mudanças microestruturais apenas a densidade numérica das discordâncias aumenta, enquanto as estruturas cristalinas, incluindo os parâmetros de rede dos metais, normalmente permanecem inalteradas.…”
Section: (5)unclassified
“…Guo et al (2019) citam que as pesquisas em torno da medições de tensões residuais que vêm ganhando destaque atualmente são justamente visando a busca por otimizar a calibração dos métodos que envolvem a interferência humana e, assim, melhorar sua usabilidade. Já para Gan et al (2018), erros no módulo de elasticidade e das leituras das deformações plásticas podem acarretar em divergências de valores entre as tensões calculadas. Além de que, para Kumar (2021), deformação plástica muda permanentemente a dimensão e a forma do metal, sendo que em termos de mudanças microestruturais apenas a densidade numérica das discordâncias aumenta, enquanto as estruturas cristalinas, incluindo os parâmetros de rede dos metais, normalmente permanecem inalteradas.…”
Section: (5)unclassified
“…Most of these previous reports have indicated that the crorrosion behavior and characteristics of aluminum alloy matrix is the primary corrosion. In addition, a large number of works have been concentrated on the effect of welding process on the microstructure and properties of 7A52 joint, as well as its stress corrosion sensitivity [12,13]. L. W. Zhang et al [10] adopted constant load stress corrosion test device to study stress corrosion of 7A52 aluminum alloy butt welding tensile specimen in marine atmosphere environment.…”
Section: Introductionmentioning
confidence: 99%